XVI. Yüzyıl Divan Şairi Fedayi ve İki Bahr-i Tavili - Mermer, Ahmet (Kitabevi, 2002)
Fedâyî who lived in sixteenth century in the term of Sultan Selim the second had two Bahr-i Tavîl in his divân. Bahr-i Tavîl is one of less used type of the verse. Fedâyî' s Bahr-i Tavîls were written earlier then the ones found out up to now. We accept Fedâyî's Bahr-i Tavîl as the first examples of this type of verses. These verses of Fedâyî are examined for the sake of verse and presented in addition.
XVI. Century's Poet Fedâyî and His Two Bahr-ı Tavili
Keywords: Ottoman Verse; Fedâyî and Bahr-i Tavîl